2000
DOI: 10.1074/jbc.275.11.7515
|View full text |Cite
|
Sign up to set email alerts
|

A Deficiency of Microsomal Triglyceride Transfer Protein Reduces Apolipoprotein B Secretion

Abstract: Microsomal triglyceride transfer protein (MTP) transfers lipids to apolipoprotein B (apoB) within the endoplasmic reticulum, a process that involves direct interactions between apoB and the large subunit of MTP. Recent studies with heterozygous MTP knockout mice have suggested that half-normal levels of MTP in the liver reduce apoB secretion. We hypothesized that reduced apoB secretion in the setting of half-normal MTP levels might be caused by a reduced MTP:apoB ratio in the endoplasmic reticulum, which would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…This apoB-isoform dependence upon Mttp was dramatically illustrated in studies using isolated hepatocytes from mice with liver-specific deletion of Mttp, where the secretion of apoB100 was virtually eliminated while the effects on apoB48 secretion were modest (12). Furthermore, similar studies in hetero-zygous Mttp knockout mice demonstrated that apoB100 secretion was also selectively reduced, suggesting that the secretion of apoB100 from mouse liver may be limited by as little as a 50% reduction in Mttp availability (7,13).…”
mentioning
confidence: 61%
“…This apoB-isoform dependence upon Mttp was dramatically illustrated in studies using isolated hepatocytes from mice with liver-specific deletion of Mttp, where the secretion of apoB100 was virtually eliminated while the effects on apoB48 secretion were modest (12). Furthermore, similar studies in hetero-zygous Mttp knockout mice demonstrated that apoB100 secretion was also selectively reduced, suggesting that the secretion of apoB100 from mouse liver may be limited by as little as a 50% reduction in Mttp availability (7,13).…”
mentioning
confidence: 61%
“…In DIO mice ( Table 1 ), the reductions in TPC were due to reductions in nonHDL-C and HDL-C, a plasma lipid profi le that is similar to that observed in ApoB +/ Ϫ or MTP +/ Ϫ mice (20,21). In addition, neither apoB nor MTP ASO had any effect on plasma TG, which was not surprising given the relatively low plasma TG levels of this model.…”
Section: Analysis Of Hepatic Fatty Acid Synthesismentioning
confidence: 87%
“…Studies of rabbits and hamsters treated with MTP inhibitor drugs have shown that an ϳ50% reduction in MTP activity effectively lowered plasma lipoprotein levels and had only minor (but definitive) effects on triglyceride deposition in liver cells (7,9). Even though simple mild hepatic steatosis often has a benign course in nondiabetic individuals, ϳ20% of individuals with type 2 diabetes develop nonalcoholic steatohepatitis that ultimately results in cirrhosis in 20 -30% of the cases (42).…”
Section: Discussionmentioning
confidence: 99%